2019
DOI: 10.1002/art.41040
|View full text |Cite
|
Sign up to set email alerts
|

What Level of Inflammation Leads to Structural Damage in the Sacroiliac Joints? A Four‐Year Magnetic Resonance Imaging Follow‐Up Study of Low Back Pain Patients

Abstract: Objective. Sacroiliac (SI) joint bone marrow edema (BME) is considered to be pivotal in the detection of early spondyloarthritis. However, the link between BME and development of spondyloarthritis-related bone remodeling remains unclear. This study was undertaken to investigate the evolution of BME and structural lesions in the SI joints over time.Methods. Baseline and 4-year follow-up magnetic resonance imaging scans were conducted in 604 patients ages 18-40 years who were referred with low back pain to an ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 31 publications
2
9
0
Order By: Relevance
“…However, in a post hoc analysis of women who had previously given birth in the groups of disc herniation, cleaning staff, and long‐distance runners, we found very limited BME, fat lesions, and sclerosis and no erosion, backfill, and ankylosis, which suggests that SI joint findings on MRI in postpartum women may diminish over time. This is in agreement with the observation of Arnbak et al (25), who observed that small and intermediate SI joint BME lesions on MRI in patients with low back pain were mostly transient and rarely developed into extensive BME or structural lesions such as fat lesions and erosion.…”
Section: Discussionsupporting
confidence: 93%
“…However, in a post hoc analysis of women who had previously given birth in the groups of disc herniation, cleaning staff, and long‐distance runners, we found very limited BME, fat lesions, and sclerosis and no erosion, backfill, and ankylosis, which suggests that SI joint findings on MRI in postpartum women may diminish over time. This is in agreement with the observation of Arnbak et al (25), who observed that small and intermediate SI joint BME lesions on MRI in patients with low back pain were mostly transient and rarely developed into extensive BME or structural lesions such as fat lesions and erosion.…”
Section: Discussionsupporting
confidence: 93%
“…In summary, these studies further confirm that pregnancy and extensive physical activity are possible non-SpA-related causes of low-grade sacroiliac joint BME, as was earlier observed for obesity and age-related degeneration [41]. This low-grade BME was shown to have a different progression compared to extensive BME in a study including 604 unselected low back pain patients including an unknown proportion of SpA patients.…”
Section: The Spectrum Of Mri Findings Between Healthy and Diseased -Impact Of Mechanical Stresssupporting
confidence: 82%
“…In this group, low-grade BME was prevalent but mostly transient, and only rarely developing into extensive BME or structural lesions. In contrast, extensive BME strongly predicted the development of new structural lesions in the same region [41].…”
Section: The Spectrum Of Mri Findings Between Healthy and Diseased -Impact Of Mechanical Stressmentioning
confidence: 91%
“… 30 Extensive sacroiliac bone marrow oedema is also a strong predictor of the development of structural lesions, in contrast to limited or intermediate inflammatory lesions. 31 Male sex was shown to be a predictor of future sacroiliac inflammation detected by MRI in patients with IBP of short duration. 18 It is also known to be a predictor of treatment response in both radiographical 32 and non-radiographical 33 axSpA and to be associated with accelerated radiographical progression at the levels of the sacroiliac joints 34 and the spine.…”
Section: Discussionmentioning
confidence: 95%